Bivalve mollusc circadian clock genes can run at tidal frequency. Issue 1918 (15th January 2020) - Tran, Damien; Perrigault, Mickael; Ciret, Pierre; Payton, Laura
Abstract : Marine coastal habitats are complex cyclic environments as a result of sun and moon interactions. In contrast with the well-known circadian orchestration of the terrestrial animal rhythmicity (approx. 24 h), the mechanism responsible for the circatidal rhythm (approx. 12.4 h) remains largely elusive in marine organisms. We revealed in subtidal field conditions that the oyster Crassostrea gigas exhibits tidal rhythmicity of circadian clock genes and clock-associated genes. A free-running (FR) experiment showed an endogenous circatidal rhythm. In parallel, we showed in the field that oysters' valve behaviour exhibited a strong tidal rhythm combined with a daily rhythm. In the FR experiment, all behavioural rhythms were circatidal, and half of them were also circadian. Our results fuel the debate on endogenous circatidal mechanisms. In contrast with the current hypothesis on the existence of an independent tidal clock, we suggest that a single 'circadian/circatidal' clock in bivalves is sufficient to entrain behavioural patterns at tidal and daily frequencies.